Analisis Komparatif: Pengaruh Makroekonomi pada Kinerja Reksa Dana Saham Syariah dan Konvensional - Muhamad Faisal Pasha Ridwan; Muhamad Umar Mai (Fakultas Ekonomi dan Bisnis Islam, 2021)
This study aims to compare the performance of Islamic stock mutual funds and conventional stock mutual funds with different operating systems so that can be recommended for investors in choosing the type of mutual fund. This study also aims to determine the effect of macroeconomic factors on the performance of these equity funds. The sample used in this study were 5 investment manager companies that issued Islamic stock mutual fund products and conventional stock mutual funds in the 2010-2019 period and were selected through purposive sampling technique. This type of research is quantitative research. The data used is secondary data obtained from OJK published reports. The results of this study indicate that there is no significant difference between the performance of conventional equity mutual funds and Islamic stock mutual funds. In addition, three independent variables in the study, namely inflation rate, exchange rate, and interest rate have a significant effect on the performance of Islamic equity mutual funds. For conventional equity mutual funds, the results show that the inflation rate and interest rate variables have a significant effect, while the exchange rate variable has a negative but not statistically significant effect on the performance of conventional equity mutual funds.